Going, going, gone! with the Pain and the Great One - Blume, Judy (Delacorte Press, 2008)
Further adventures of first-grader Jake "the Pain" and his sister, third-grader Abigail "the Great One," include a trip to the beach with Grandma, to a county fair with Aunt Diana, and to a mall with Dad.